2012
DOI: 10.1590/s0104-11692012000200025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life in a palliative care context: an integrative literature review

Abstract: The use of scales that have been validated and standardized for different cultures is very useful for identifying demands in the field of Palliative Care and implementing the most appropriate care. This integrative literature review focuses on instruments assessing the Quality of Life of patients under Palliative Care through a journal search in electronic databases. The study consisted of 49 papers identified in Medline/PubMed, of which 18 met the inclusion criteria previously defined. Information con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The following reports describe this: At this moment, the importance of professionals' support and communication with the families of patients who will begin to receive palliative care should be emphasized, as this contact is essential to provide high quality services. 24 Based on this fact, the importance of establishing connections between the team and caregiver/family member stands out, as it promotes trust among those involved. The fact that they feel like they have company and are not alone enables most caregivers to express their feelings more easily.…”
Section: Family Members/caregivers' Feelings About Palliative Carementioning
confidence: 99%
“…The following reports describe this: At this moment, the importance of professionals' support and communication with the families of patients who will begin to receive palliative care should be emphasized, as this contact is essential to provide high quality services. 24 Based on this fact, the importance of establishing connections between the team and caregiver/family member stands out, as it promotes trust among those involved. The fact that they feel like they have company and are not alone enables most caregivers to express their feelings more easily.…”
Section: Family Members/caregivers' Feelings About Palliative Carementioning
confidence: 99%
“…It is also noticed that despite the advances, the complexity of the situations involving this care modality brings difficulties to health professionals regarding the management of physical, psychosocial and spiritual symptoms and suffering that directly interfere in the QoL. Therefore, assessment measures are necessary to identify the demands in evaluating the services and care offered, and mainly in the definition of more suitable and individualized conducts (6) . Thus, the objective of this study was to analyze the relationship between social support, QoL and depression in patients eligible for PC attended by PHC of a municipality in the interior of Minas Gerais state, Brazil.…”
mentioning
confidence: 99%
“…It is worth mentioning that during the initial search, two records of integrative review were found, one of which addressed the POS validation studies 14 and the other, the impact of APCA POS as a tool to improve patient care quality and their families 15 (though, been secondary sources of data, these two studies were not eligible). …”
Section: Methodological Pathwaymentioning
confidence: 99%